Cold Atom Cloud with High Optical Depth Measured with Large Duty Cycle - 张骏 顾振杰 钱鹏 韩枝光 陈洁菲 (Chinese physics letters, 2015)
We present a cold atom system with a dark-line two-dimensional magneto-optical trap, to increase the atomic density by suppressing the atomic radiation pressure. Optical depth （OD） and duty cycle are used to evaluate the system performance. We demonstrate a 100% increase in OD with the dark line, and obtain an ultrahigh OD of 264 with 10% for the duty cycle. Also, with an efficient dark line region, the OD could maintain above i00 with duty cycle as high as 30%. The cold atomic ensemble with an ultrahigh OD with a 10%-30% duty cycle is particularly advantageous in quantum i~formation processing and communication.